Estimation of lightning impulse insulation strength of two seriesdielectrics using the least square technique - Shwehdi, M.H. (1997)
In this paper, the least square (LS) estimation technique was used to estimate the total critical flashover (CFO) for combinations of two insulating materials from the experimental data obtained. This method had acceptable accuracy when applied to the total population of the two-component combinations but lost some accuracy for some of the sub-sets of the two materials